History of Iranian Literature - Rypka, Jan (1968)
Written in collaboration with O. Klíma, V. Kubíčková, F. Tauer, J. Bečka, J. Cejpek, J. Marek, I. Hrbek and J. T. P. de Brujn. Edited by K. Jahn; also on Old Persian inscriptions.